MORBUS HANSEN PAUSIBASILER TIPE BORDERLINE-BORDERLINE DENGAN LESI TUNGGAL PADA SEORANG ANAK LAKI – LAKI: SATU LAPORAN KASUS JARANG - Widhiati, Suci; Widyastuti, Zilpa; Fiqnasyani, Siti Efrida (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Background: Morbus Hansen (MH) is a chronic infectious disease caused by Mycobacterium leprae. Diagnosis of MH was established based on cardinal signs on clinical examination, AFB examination on ear lobe serum and histopathological examinations. Children with single lesion MH (AFB negative) without any neurological complaints are treated with single dose of Rifampicin-Ofloxacin-Minocycline (ROM) combination therapy. This case was reported because of the rarity of children MH and the importance of early diagnosis to avoid disability risks. Case: A 12-year-old boy with single lesion borderline-borderline (BB) paucibacillary MH presented with white-reddish patch on cheeks that getting wider since 2 years ago. Dermatological status obtained in left maxila region showed hypopigmented and hyperpigmented patch with erythematous base, solitary, well defined, 0.5x1.5 cm in size with central clearing forming a punched out lesion. Bacteriological and histopathological examinations with Hematoxylin-Eosin and Fite-Faraco staining showed AFB negative result, but serological examination of anti-PGL-1 antibodies showed high titers (IgM=845 u/ml, IgG=1004 u/ml). The patient was given single dose of Rifampicin 450mg, Ofloxacin 400mg, Minocycline 100mg (ROM) and atopiclair® lotion applied to the lesion twice a day. Evaluation on the third week showed improvement with disappearance of redness and punched out lesion. Discussion: Patient in this case is a rare incident because it occured in children with no contact history and had never lived in MH endemic area. Because of Mycobacterium leprae’s transmission route is still not known, other factors such as genetics, immunity, environmental conditions and non-human vectors need more attention in breaking the chain of MH transmission.